Pengaruh Pendapatan, Pinjaman, Literasi Ekonomi, dan Gaya Hidup terhadap Pengeluaran Konsumsi Rumah Tangga di Desa Mojosari Kecamatan Kras Kabupaten Kediri - Yulita, Nuralif Nanda; Manunggal, Syafrudin Arif Marah (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This research aimed to determine the effect of income, loans, economic literacy, and lifestyle on household consumption expenditure in Mojosari Village Kras District Kediri Regency. The research sample consisted of 94 households in Mojosari Village using the Slovin technique. This research used multiple linear regression analysis with a dummy variable in SPSS 20. The results explained that income and loans partially had a significant effect on household consumption expenditure, while economic literacy and lifestyle partially had no significant effect on household consumption expenditure in Mojosari Village Kras District Kediri Regency. Income, loans, economic literacy, and lifestyle simultaneously had a significant effect on household consumption expenditure in Mojosari Village Kras District Kediri Regency.